Study on the Function and Planning of Urban River Ecological Corridor - Huang, Yan; Wang, Dong (The Global Environmental Engineers, 2024)
This study investigates the functions and planning principles of urban river ecological corridors, highlighting their vital role in urban ecosystems. Urban rivers, which include both waterways and riparian zones, provide essential ecosystem services such as habitat provision, temperature regulation, pollutant filtration, and flood mitigation. However, rapid urbanization has led to the degradation of these corridors, resulting in habitat fragmentation, reduced biodiversity, and compromised ecological integrity. The paper reviews global efforts and strategies for urban river restoration, emphasizing the significance of ecological methods and public participation in the planning process. A case study of the Yuhangtang River in Hangzhou, China, exemplifies various restoration approaches, including traditional flood control, ecological restoration, and landscape design, all assessed using a multi-criteria decision-making (MCDM) framework. The findings indicate that employing the MCDM tool can facilitate planning that integrates the functions of river ecological corridors. Additionally, plans that achieve a balance of ecological, economic, social, and aesthetic benefits are more likely to gain public acceptance.